Platelet-rich plasma improves initial bone remodeling - Edy Machmud; Bahruddin Thalib; Mochammad Dharmautama; Acing H. Mude; Irfan Dammar; Muhammad Ikbal (Journal of Dentomaxillofacial Science, 2020)
Objective: To compare the osteoblast cell formation process after installation implant with and without added of platelet-rich plasma (PRP). Methods: Twenty-four male rabbit were selected by purposive sampling, divide into two groups. Group 1 implant with added PRP were installation in the distal part of the thigh bone 12 male rabbits, Group 2 implants without the addition of PRP mounted on the distal part of the thigh bone 12 male rabbits. All rabbits in euthanasia after 0, 7, 14, and 28 days were then analyzed histologically to determine the formation of osteoblast cells. Results: There is increased formation of osteoblast cell formation in implant installation with the addition of PRP when compared with implants without PRP as time increases. Conclusion: Administration of PRP in implants can speed up and increase osteoblast cell formation.